Implementation and testing of a conformance platform for IEEE 1901.1 Power Line Communication Standard. Issue 1 (July 2021) - Amaro, Nuno; Saragoça, João; Cartaxo, Ricardo; Yang, Wei; Yi, Ren
Abstract: IEEE 1901.1 Standard for Medium Frequency (less than 12 MHz) Power Line Communications for Smart Grid Applications was officially released on 2018. This standard brings new possibilities for power line communications, as the used frequency range allows for broader band and higher bit rates when compared to other PLC communication standards. In this scope, this paper presents a conformance platform that allows testing compliance of devices implementing the standard. This conformance-testing platform is then used to test the station and concentrator devices from three different manufacturers, using the data link layer tests as one example, highlighting the capabilities of the platform and simultaneously evaluating the current status of development of these devices (with regards to standard compliance). Results of these tests are also included.